2019
DOI: 10.2147/lctt.s180692
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of smoking on frequency and spectrum of <em>K-RAS</em> and <em>EGFR </em>mutations in treatment naive Indonesian lung cancer patients</p>

Abstract: Background: Indonesia has the highest cigarette consumption in the world. We explored the clinical impact of smoking on the prevalence of EGFR and K-RAS mutations and survival in this prospective study. Methods: 143 treatment naive lung cancer patients were recruited from Persahabatan Hospital, a national tertiary hospital. DNA from cytological specimens had been extracted and genotyped for both EGFR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…23 In addition, Syahruddin et al, as the first study to identify KRAS mutations in lung cancer in Indonesia, showed a lower incidence of KRAS mutations compared with populations worldwide (7% vs 31%). 24,25 The occurrence of KRAS mutations also often coincides with mutations in other oncogenes or tumor suppressor genes. Co-mutations between KRAS and TP53 were the most prevalent and were related to the poorest outcomes in all pharmacological approaches including targeted therapy, chemotherapy, and radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…23 In addition, Syahruddin et al, as the first study to identify KRAS mutations in lung cancer in Indonesia, showed a lower incidence of KRAS mutations compared with populations worldwide (7% vs 31%). 24,25 The occurrence of KRAS mutations also often coincides with mutations in other oncogenes or tumor suppressor genes. Co-mutations between KRAS and TP53 were the most prevalent and were related to the poorest outcomes in all pharmacological approaches including targeted therapy, chemotherapy, and radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies show that Asian populations have significant lower KRAS mutation incidence than that in the Caucasian and Afro-American populations [ 37 , 38 ]. As for Europe, even in Asia there is a wide range in the mutation frequencies among countries, with the highest values in Vietnam (21%, close to European populations) and the lowest in China (8.4–13%), Japan (10%) and Indonesia (7%) [ 33 , 39 , 40 , 41 , 42 ].…”
Section: Kras Mutations In Population-based Cohorts Of Lung ...mentioning
confidence: 99%
“…Apart from relating the nature of disease and prognosis of lung cancer, KRAS mutation exhibit an association with several clinical and demographic factors, including ethnic variability and environmental alteration ( 5 - 8 ). Several studies showed that the Asian population has lower KRAS mutation incidence compare with the Western and Black populations ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from relating the nature of disease and prognosis of lung cancer, KRAS mutation exhibit an association with several clinical and demographic factors, including ethnic variability and environmental alteration ( 5 - 8 ). Several studies showed that the Asian population has lower KRAS mutation incidence compare with the Western and Black populations ( 7 ). In the Chinese population, the prevalence of KRAS mutation was 13.1% in lung adenocarcinoma ( 9 ), wherein Indonesian population, KRAS mutation was about 7% in all types of lung cancer ( 10 ).…”
Section: Introductionmentioning
confidence: 99%